Talk with alumni unlocking career success: essential attitude for job security - Ismail, Zuriati; Kerk, Lee Chang; Ibrahim, Nur Syafikah; Mat Zin, Siti Hasma Hajar; Adnan, Nur Aina Khadijah (Universiti Teknologi MARA, Johor, 2024)
Despite the fact that you are still enrolled in classes, what transpires after graduation matters greatly. Only a few people can talk confidently about having the knowledge of what's out there and how to prepare for the challenge. The Institute of Labour Market and Institution reports that data from industrialised nations with high rates of youth unemployment indicates that this is due to young people are more likely to experience psychological consequences such as feelings of shame, rejection, confusion, anxiety, insecurity, depression, loneliness, and unloved.